REVIEWS (Heythrop journal, 1967)
Book reviewed in this article: Essays on Old Testament History and Religion. By Albrecht Alt. Translated by R. A. Wilson. Deuteronomy. By Gerhard von Rad. Translated by Dorothea Barton. The Resurrection of Christ. By S. H. Hooke. Interpreting the Resurrection. By Neville Clark. The Resurrection in the Plan of Salvation. By Joseph Comblin. Studies in the Apostolic Fathers and their Background. By L. W. Barnard. Early Christian Thought and the Classical Tradition: Studies in Justin, Clement and Origen. By Henry Chadwick. Justin Martyr: His Life and Thought. By L. W. Barnard. Éphrem de Nisibe: Commentaire de l'Évangile Concordant ou Diatessaron. Translated by Louis Leloir, o.s.b. Ministère et Sainteté. By Rémi Crespin. The Desert a City. By Derwas J. Chitty. The Theology of Unity. By Muhammad‘Abduh. Translated from the Arabic by Ishaq Musa'ad and Kenneth Cragg. Baptism Today and Tomorrow. By G. R. Beasley-Murray. The Vision of the Past. By Pierre Teilhard de Chardin. Translated by J. M. Cohen. Man's Place in Nature. By Pierre Teilhard de Chardin. Translated by René Hague. Teilhard de Chardin and the Mystery of Christ. By Christopher F. Mooney, s.j. The Church in the thought of Bishop John Robinson. By Richard P. McBrien. Opera Omnia. By Henry More. Edited with an Introduction by Serge Hutin. Vol. I: Henry More. By Serge Hutin. Throne and Altar. The Political and Religious Thoughr of Joseph de Maistre. By Richard Allen Lebrun. Lamennais and England. The Reception of Lamennais's Religious Ideas in England in the Nineteenth Century. By W. G. Roe. The Church of England 1900–1965. By Roger Lloyd. Uses of Sociology. Edited by J. D. Halloran and Joan Brothers.